Exogenous cortisol facilitates responses to social threat under high provocation - Bertsch, Katja; Böhnke, Robina; Kruk, Menno R.; Richter, Steffen; Naumann, Ewald (Hormones and behavior, 2011)
Stress is one of the most important promoters of aggression. Human and animal studies have found associations between basal and acute levels of the stress hormone cortisol and (abnormal) aggression. Irrespective of the direction of these changes - i.e., increased or decreased aggressive behavior - the results of these studies suggest dramatic alterations in the processing of threat-related social information. Therefore, the effects of cortisol and provocation on social information processing were addressed by the present study. After a placebo-controlled pharmacological manipulation of acute cortisol levels, we exposed healthy individuals to high or low levels of provocation in a competitive aggression paradigm. Influences of cortisol and provocation on emotional face processing were then investigated with reaction times and event-related potentials (ERPs) in an emotional Stroop task. In line with previous results, enhanced early and later positive, posterior ERP components indicated a provocation-induced enhanced relevance for all kinds of social information. Cortisol, however, reduced an early frontocentral bias for angry faces and - despite the provocation-enhancing relevance - led to faster reactions for all facial expressions in highly provoked participants. The results thus support the moderating role of social information processing in the ‘vicious circle of stress and aggression’.